A community based study on age of menarche among adolescent girls in Aligarh - Tarannum, Farha; Khalique, Najam; Eram, Uzma (International Journal Of Community Medicine And Public Health, 2017)
Background: Age at menarche reflects the health status of a population. This marks the beginning of sexual maturation and is affected by various factors. This study measured the menarcheal age of adolescent girls in Aligarh and explored factors that could influence the onset of menarche. Methods: A descriptive cross-sectional study in schools under Aligarh Muslim University, Aligarh was undertaken. A total of 422 girls were taken by systematic random sampling with probability proportionate to size. Data was analysed statistically by ANOVA and post hoc Scheffe test using SPSS Version 20. Results: Majority of the study population (69.9%) had attained menarche between 12-14 years. The mean age of menarche is 12.52±1.415. On analysis of variance (ANOVA) testing, the age of menarche was significantly associated with socioeconomic class (p=0.002). On applying post hoc Scheffe test there was a significant difference in the mean age of menarche between class 1 and class 5 (p=0.01). Conclusions: In this study most of the girls attained menarche between 12-14 years. Socio economic class and birth order had influenced the age of menarche. Mothers were main source of information on attainment of menarche.